The effect of peer counseling-based health education in reducinganxiety among students at University Muhammadiyah Surakarta - Ardhana, Calysta Vinella; Widodo, Arif (Science Midwifery, 2025)
Anxiety is a prevalent psychological issue among university students, particularly nursing students who face intense academic and clinical demands. According to the World Health Organization (WHO, 2024), the global prevalence of anxiety disorders increased by 26% after the COVID-19 pandemic, while national data from Indonesia (Riskesdas, 2019; 2021) reported emotional mental disorders affecting 9.8% of the productive-age population. Unmanaged anxiety can impair concentration, reduce academic performance, and negatively affect mental health. One promising non-pharmacological approach is health education through peer counseling, which utilizes emotional support among students at similar academic levels. This study aimed to analyze the effect of peer counseling-based health education on nursing students’ anxiety levels. A quasi-experimental one-group pretest–posttest design was applied, involving 50 sixth-semester nursing students from the Faculty of Health Sciences, Universitas Muhammadiyah Surakarta, selected using purposive sampling. Data were collected using questionnaires measuring knowledge, attitudes, and behaviors, and the State-Trait Anxiety Inventory (STAI-T) to assess anxiety levels. Statistical analysis was performed using the Paired Sample t-test and Wilcoxon Signed Rank Test. The results showed significant improvements in students’ knowledge, attitudes, and behaviors after the peer counseling intervention (p < 0.05). The mean anxiety score decreased from 50.98 to 46.60 (p < 0.05), indicating a substantial reduction in anxiety levels. These findings confirm that peer counseling-based health education effectively enhances student understanding and alleviates anxiety. The study recommends implementing peer counseling as a promotive and preventive strategy to support mental health among nursing students, especially during high-pressure academic periods.